2022
DOI: 10.18485/meattech.2022.63.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Goat Meat Consumption Patterns and Preferences in Three Provinces of Kabylia Region in Algeria Compared to Other Meat Species: Results of an Online Survey

Abstract: This study aimed to investigate, using an online survey, the patterns/frequency of meat consumption, and preferences from several meat types in Kabylia region in Algeria and within three provinces (Tizi-Ouzou, Bejaia, and Bouira). Thus, we specifically examined in this work the consumption of goat meat compared to lamb, beef, horse, camel, and chicken. The attempt is to understand the underlying factors of consumer perception and purchasing behaviour/decisions of goat meat through an exploratory survey on a ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Moreover, the availability of camel meat in the different regions of Algeria, in the South in the comparison with the North of the country, could influence its consumption frequency. A recent study reported by Lamri et al [14], using an online survey (n = 665 consumers), showed that camel meat is not well appreciated and eaten by consumers from the region of Kabylia (Algeria), 54.3% of them never consumed it, only 1.6% eat it always, 35% sometimes and 9.1% rarely. These results may be due to habits and traditions and the limit production and availability of camel meat in this region and in the North of the country in general.…”
Section: Camel Meat Consumption and Meat Products In The World And In...mentioning
confidence: 98%
“…Moreover, the availability of camel meat in the different regions of Algeria, in the South in the comparison with the North of the country, could influence its consumption frequency. A recent study reported by Lamri et al [14], using an online survey (n = 665 consumers), showed that camel meat is not well appreciated and eaten by consumers from the region of Kabylia (Algeria), 54.3% of them never consumed it, only 1.6% eat it always, 35% sometimes and 9.1% rarely. These results may be due to habits and traditions and the limit production and availability of camel meat in this region and in the North of the country in general.…”
Section: Camel Meat Consumption and Meat Products In The World And In...mentioning
confidence: 98%
“…The consumers' sense of smell play a significant role in determining meat eating quality (Das & Rajkumar, 2010;Goetsch et al, 2011;Pophiwa et al, 2020;Webb et al, 2005). Despite goat meat being of satisfactory eating quality, it is not as preferred as other meat species (Lamri et al 2022). For example, chevon is not preferred over lamb/mutton and beef due to its tough texture and strong peculiar flavor, particularly in western countries (Webb et al, 2005).…”
Section: Intrinsic Factors Affecting Goat Meat Qualitymentioning
confidence: 99%
“…The acceptance of goat meat is also hindered by religious and caste dogma (Webb et al, 2005). So, it is necessary to produce quality goat meat to promote its beneficial part among reluctant consumers (Pophiwa et al, 2020;Lamri et al 2022). In the following sections, the main intrinsic factors that impact goat meat quality are described.…”
Section: Intrinsic Factors Affecting Goat Meat Qualitymentioning
confidence: 99%